Faith Education According to Badi Al-Zaman Saeed Al-Nursi - Peshraw Hama Ali Abdullah; Abdlfattah Hussein Sulaiman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
After the collapse of the Ottoman Empire and the sharing of its properties among the modern colonial countries, the modern state of Turkey was established by Mustafa Ataturk. By all concepts, it is very far from the commitment of the Ottoman Empire to the principles and legislation of Islam and with all those who seek to apply Western civilization, including it without scrutiny, in what benefits the country and the people or does not benefit, trying to keep Muslim youth away from the morals of their religion and Sharia. Imam Bediuzzaman Saeed Nursi rose up carrying the torch of Islamic Sharia to light the path of the nation and guide it to what is in its best interest and the best of its sons, defying all foreign ideas on the nation. At that time and until now, which he called (Risala al-Nur), And this research sheds light on an important part of the Risala al-Nur colleges, which is faith education. The researcher tried hard in it to shed light on the effort of this imam in this part